An epidemiological investigation to determine the prevalence and clinical manifestations of slow-moving finished cattle presented to slaughter facilities() - Lee, Tiffany L (Transl Anim Sci, 2018)
Cattle mobility is routinely measured at commercial slaughter facilities. However, the clinical signs and underlying causes of impaired mobility of cattle presented to slaughter facilities are poorly defined. As such, the objectives of this study were 1) to determine the prevalence of impaired mobility in finished cattle using a 4-point mobility scoring system and 2) to observe clinical signs in order to provide clinical diagnoses for this subset of affected cattle. Finished beef cattle (n = 65,600) were observed by a veterinarian during the morning shift from six commercial abattoirs dispersed across the United States; the veterinarian assigned mobility scores (MS) to all animals using a 1–4 scale from the North American Meat Institute’s Mobility Scoring System, with 1 = normal mobility and 4 = extremely limited mobility. Prevalence of MS 1, 2, 3, and 4 was 97.02%, 2.69%, 0.27%, and 0.01%, respectively. Animals with an abnormal MS (MS > 1) were then assigned to one of five clinical observation categories: 1) lameness, 2) poor conformation, 3) laminitis, 4) Fatigued Cattle Syndrome (FCS), and 5) general stiffness. Of all cattle observed, 0.23% were categorized as lame, 0.20% as having poor conformation, 0.72% as displaying signs of laminitis, 0.14% as FCS, and 1.68% as showing general stiffness. The prevalence of lameness and general stiffness was greater in steers than heifers, whereas the prevalence of laminitis was the opposite (P < 0.05). FCS prevalence was higher in dairy cattle than in beef cattle (0.31% vs. 0.22%, respectively; P ≤ 0.05). These data indicate the prevalence of cattle displaying abnormal mobility at slaughter is low and causes of abnormal mobility are multifactorial.